2012
DOI: 10.1097/pec.0b013e3182440b9b
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis

Abstract: A model using objective findings had limited accuracy for predicting hospitalization after emergency department evaluation for bronchiolitis. In these infants with moderate to severe bronchiolitis, however, initial SpO(2) was the best predictor of hospital admission and of longer LOS. Efforts to better define and manage hypoxemia in bronchiolitis may be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 25 publications
7
54
2
Order By: Relevance
“…Our findings are consistent with those of Corneli et al, 30 who identified RDAI score, SaO 2 , and respiratory rate as predictors of hospitalization in bronchiolitis. On the contrary, Destino et al 16 found that RDAI sum scores did not discriminate well between admitted and discharged patients, but the item on retractions did.…”
Section: 18supporting
confidence: 83%
“…Our findings are consistent with those of Corneli et al, 30 who identified RDAI score, SaO 2 , and respiratory rate as predictors of hospitalization in bronchiolitis. On the contrary, Destino et al 16 found that RDAI sum scores did not discriminate well between admitted and discharged patients, but the item on retractions did.…”
Section: 18supporting
confidence: 83%
“…A previously reported multicenter randomized controlled trial comparing just a single dose of dexamethasone with placebo showed no difference between the 2 groups in the decision about hospital admission at 4 hours and the length of hospital stay. 22 Although we also found no difference in readiness for discharge at 4 hours, we found an overall geometric mean shorter length of stay for patients treated with dexamethasone (and salbutamol), probably because the treatment was targeted to patients with eczema or a first-degree relative with asthma, rather than the entire population with bronchiolitis.…”
Section: Discussionmentioning
confidence: 60%
“…Because the criteria we tested were present in 66% of a similar population of patients with a first episode of bronchiolitis, 22 applying this generalizable treatment could alleviate the overall burden of this disease in many clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The study by Corneli et al assessed clinical decision making, that is, which data are used by emergency department physicians to identify patients who require hospitalization, and did not study the appropriate use of oximetry in the decision-making process. Schuh et al attempted to answer a difficult question, the appropriateness of oxygen saturation in the clinical setting.…”
mentioning
confidence: 99%